Numerical analysis of the photovoltaic system inspection with active cooling - Ahmed Hasan Mohammed; Ghanim Thiab Hasan; Kamil Jadu Ali (Institute of Advanced Engineering and Science, 2021)
The use of solar energy may replace the present fossil fuel or gas to produce electricity. The goal of this study is to set up a simulation model to survey the performance of a photovoltaic thermal system (PV/T) based on the computational fluid dynamics (CFD) method. Ansys fluent software has been used for the simulation procedure. The electrical panel output and its efficiency were investigated numerically. In addition, the effect of variations in absorbed radiation on inlet fluid and absorber panel temperature on the system performance was investigated. The study was conducted for three cases, in a first case, where there is no refrigerant in the system and in the latter case, at constant fluid rate of the pump, whereas the third case with optimal pump operation. The numerical findings obtained from CFD simulators have been compared with the test records of the experimental results of the literature. The two results have a good agreement. From the obtained results, it can be noted that the system shows a good improvement for the electric net efficiency level of 3.52% with a lower reduction of the thermal system efficiency of 1.96% in comparison to the system when using the constantly high flow rate.